LATINISMS IN LEGAL TEXTS – A CONTRASTIVE APPROACH POLISH-GERMAN - WOŹNIAK, Joanna (Comparative Legilinguistics, 2018)
Terms and Phrases of Latin origin have been incorporated into the contempo-rary Continental and Anglo-Saxon legal systems. Latin borrowings are a sign of the common cultural and social origin of European countries. Most of the bor-rowings have been adapted on the phonetic, morphological and grammatical level. Others, like Latin proverbs, terms and phrases retained their original pronunciation and orthography. The main goal of this article is to discuss the essence of Latinisms, in particular their place in the contemporary linguistics and their function in legal texts. In the second part the article presents the results of the analysis of the Latin struc-tures, used in Polish and German legal texts, available in the Eur-lex databases. The research is aimed not only at comparing the occurrence of Latin terms, phrases or proverbs in legal documents, but also at showing the way of their introducing to the text and discussing the consequences of their usage for the understanding of the law.